FUNDAMENTALS OF STRATEGIC MANAGEMENT IN THE COMPLEX OF OPERATING ACTIVITY OF THE ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In modern context of a changing market environment, enterprises are faced with the need to combine long-term strategic guidelines with effective operational activities. When entering global competition, strategic management becomes a key factor in ensuring operating stability and business development in the future.The purpose of the article. The purpose of the article is to identify the basic approaches to the formation of strategic management in the complex of operational activity of the enterprise and to substantiate the directions of their practical implementation.Methods. The methodological basis of the study is methods that include the analysis and synthesis of scientific literature, systematic approach, methods of comparative analysis and generalization of practical experience of functioning of enterprises in different fields.Results. The results of the study made it possible to determine the principles of building effective interaction between the strategic goals of the enterprise and its operational processes. The integrated management model is proposed, which takes into account the specifics of operating activities and ensures strategic results in.Conclusions. The allocation of the basic principles of strategic management in the complex of operational activity of the enterprise will allow to form a close relationship between strategy and operational activity and is a prerequisite for improving the competitiveness of the enterprise, optimizing the use of its resources and the key element of ensuring its positive development in the dynamic market environment.
Keywords: enterprise, strategy, management, strategic management, operational activity, competitiveness, business processes, operational management, management decisions, efficiency of activity, adaptability of the enterprise, resource support.